Pengaruh Kualitas Pelayanan (O-Ranger Mobile), Ketepatan Waktu, Tarif Pengiriman Terhadap Kepuasan Pelanggan - Nur Salim, Ahmad Farisi; syafi'i, Imam; Arifin, Moh. Samsul (Ecobuss, 2024)
This research aims to determine several factors that influence customer satisfaction which consists of the following variables: quality of administration (O-ranger mobile), ideality, synchronization and level of delivery rates on consumer satisfaction within the Kraksaan Post Office. The approach to this research uses a quantitative descriptive method, for the data sample in this research using purposive sampling data collection, namely by distributing questionnaires to customers of the Kraksaan branch post office. The results of research on Service Quality (O-ranger Mobile), timeliness of goods delivery, and goods delivery rates have a partial and simultaneous effect on customer satisfaction. However, there are two variables that have a significant effect in this research and one variable has no partial effect on Customer Satisfaction.